Clinical Study on the Treatment of Female Stress Urinary Incontinence With Modified Buzhong Yiqi Decoction - Zhou, Feifei; Chen, Chen; Shi, Jiani; Zhou, Qianru; Jin, Lijun; Ma, Xiaofang (Frontiers in Surgery, 2022)
Purpose: To study the clinical application value of Modified Buzhong Yiqi Decoction in the treatment of female stress urinary incontinence (SUI). Methods: A total of 103 female SUI patients were included in this study, 13 were lost to follow-up, and the final number of studies was 90. Chronic respiratory disease, hypertension, and diabetes were recorded. All patients were treated with Buzhong Yiqi Decoction alone for 4 weeks. The subjective symptoms, the degree of urinary incontinence, the curative effect of Jiawei Buzhong Yiqi and the related factors of curative effect were evaluated before treatment, 1 month after treatment and 1 year after treatment. Results: 1 month after Modified Buzhong Yiqi Decoction treatment, compared with before treatment, the PGI-I questionnaire was Very much better 68.89%, Much better 8.89%, A little better 12.33%, No change 8.89%, and the ICI-QSF score decreased (P<0.05), the 72-hour urine leakage frequency decreased (P<0.05); 1 year after treatment compared with before treatment, PGI-I questionnaire was Very much better 40.00%, Much better 17.78%, A little better 12.22%, No change 30.00%, ICI-QSF score decreased (P<0.05), the 72-hour urine leakage frequency decreased (P<0.05); And 1 year after treatment compared with 1 month after treatment, the ratio of Very much better at 1 year after treatment was significantly decreased (P<0.05), the score of ICI-QSF was significantly increased (P<0.05), and the 72-hour urine leakage frequency was significantly increased. (P<0.05). The correlation analysis showed that the efficacy at 1 month after treatment was negatively correlated with the severity of SUI and chronic respiratory diseases, but was not significantly correlated with age, menopause status, BMI, number of pregnancies and number of births. the efficacy at 1 year after treatment was negatively correlated with the severity of SUI, chronic respiratory disease, age and number of births, and was positively correlated with BMI, but not significantly correlated with menopause status and number of pregnancies. Conclusion: Modified Buzhong Yiqi Decoction can effectively treat SUI in women. The efficacy is related to the severity of SUI and chronic abdominal hypertension, but the long-term efficacy decreases.